Jost functions for the harmonic oscillator - Alessandrini, Victor A. (1963)
The Jost functions for the harmonic oscillator (in one and three dimensions) are computed explicitly. They are entire analytic functions in the complex E plane. Its zeros give the well-known bound states of the system. An integral representation is given for the Jost functions of the perturbed harmonic oscillator.